Ideal Formulation of Human Rights Regulation in Indonesia - Muannif Ridwan; Suhar AM; Ishaq (Yayasan Ilomata, 2023)
There have been several human rights cases in several regions in Indonesia in recent years and the ripples of conflict that have accompanied them show that there are differences in interpretation of the principles and implementation of human rights among the community. In this case, it is necessary to formulate regulations on human rights that are good and universally applicable to all groups. This research aims to offer an ideal formulation of human rights regulation in Indonesia. This research uses descriptive qualitative method or also known as literature study. This research reveals findings as one of the problem solving in human rights issues. There are three things that must be promoted as a form of struggle in maintaining human rights in Indonesia, namely strengthening the values of Pancasila as a source of human rights values, the need for a common perception of the conception of the implementation of ideal human rights in Indonesia, and the idea of a human rights education movement among the community on an ongoing basis.